OC-081 Can a "risk of coeliac disease" scoring system reduce the number of patients referred for duodenal biopsy?. (23rd September 2015) - Leeds, J S; Libzo, N; Sidhu, R; Evans, K E; Kurien, M; Hall, E J; Jandu, V S; Hopper, A D; Basumani, P; Dear, K L; McAlindon, M E; Sanders, D S
Abstract : Introduction: Coeliac disease (CD) affects 1% of the population. Despite this prevalence, the majority of individuals are undetected and patients present with atypical/subtle symptoms contributing to under diagnosis. The aim of this study was to determine the importance of different presenting characteristics and risk factors to provide a biopsy reducing strategy. Methods: Patients referred to the SYLGRG were investigated for CD using antiendomyseal and anti-tissue transglutaminase antibodies plus total IgA level. Demographics, reason for referral and comorbidities were noted. Patients with positive antibodies or IgA deficiency were offered a duodenal biopsy. Duodenal biopsies were graded using the modified Marsh criteria with grade 3 (villous atrophy) taken as diagnostic of CD. Multivariate analysis was performed to identify independent risk factors. Using these factors a coeliac risk score was constructed and tested on a second cohort (n=609). Results: 4089 patients were assessed (mean age 55.8, 2392 females). 386 patients had positive profiles (9.5%, 8.6–10.4%) of which 128 had CD (3.1%, 2.6–3.7%). Univariate analysis showed CD was associated with age <55 years (OR 2.2), IBS symptoms (OR 2.8), anaemia (OR 4.8), diarrhoea (OR 3.6), positive antibodies/need for duodenal biopsy (OR 28.7). Analysis of comorbidities revealed CD was associated with osteoporosis (OR 4.4), autoimmune disease (OR 2.3) and a family history (FHx) of CD (OR 9.0). Linear regression showed that age<55, FHx CD, Anaemia and Osteoporosis were independent risk factors for CD and these factors were then modelled and attributed scores. Age <55 = 1, anaemia=1 and EMA positive=2 giving compositae scores from 0 to 4. Scores of 0–2 corresponded to a very low risk of CD (0.84%, 0.6–1.2) and scores of 3+ corresponded to a risk of 13%–80%. Receiver operating curve analysis for the score gave an area under the curve of 0.79 (0.75–0.85, p<0.001). When applied to the validation cohort, scores of 0–2 corresponded to 0% risk of CD (0.0–0.7) and scores of 3+ corresponded to a risk of 4%–50%. Conclusion: CD accounted for one in 30 referrals. CD was associated with younger age, anaemia, positive family history and osteoporosis. Modelling of these risk factors lead to a potentially valuable scoring system that could be used to determine pre-biopsy risk of CD and in many patients avoid unnecessary biopsy. This score needs to be validated in other cohorts.